The Identification of the Studentsâ Mathematical Communication Skills Error in Form of Pictures on the Geometry of Space Subject - Kusuma, Anggun Badu; Untarti, Reni (EDUCARE, 2018)
ABSTRACT: The space geometry is one of the major subjects, which must be taken by the students of the mathematics education. The aim of the courses is to make students are able to master the form geometry in three dimensions. Competencies must be mastered include the ability to draw space, the ability to draw the slice field, and the ability to determine the extents of the slice field. Based on the competencies, the material of the space geometry was not an easy matter to be mastered by students. Students needed their imagination to visualize the shape, which came from the two-dimensional images shaped into a three dimensional or vice versa. These difficulties did not only occur on the students, but also the mathematics teachers, who had the learning process in the schools. This research belonged to qualitative descriptive study, in which the subject of this research was the class A second semester students of Mathematics Education Study Program of UMP (Muhammadiyah University of Purwokerto) in Central Java, Indonesia, in academic year 2015/2016, which belonged to the class of the shape geometry. The instruments which were used were the observation sheet and the documentation in the form of photographs or videos. The research procedures consisted of the steps in the lesson study in 3 cycles. Each cycle consisted of plan, do, and see steps. The result of the study was that the studentsâ error of mathematical communication ability was in the form of pictures on the space geometry subjects occurred on the drawing procedure in the determination of the slice field; the concept of an image in three dimensions; and the studentsâ concept in the fields analysis.KEY WORDS: Mathematical Communication Skill; Lesson Study; Geometry of Space; Form of Pictures; Studentsâ Concept.Â Â About the Authors: Anggun Badu Kusuma and Reni Untarti are the Lecturers at the Departement of Mathematics Education, Faculty of Education and Teacher Training UMP (Muhammadiyah University of Purwokerto), Jalan Raya Dukuhwaluh, Purwokerto City, Central Java, Indonesia. E-mails: anggunbadu@ump.ac.id and reniuntarti@gmail.comSuggested Citation: Kusuma, Anggun Badu & Reni Untarti. (2018). âThe Identification of the Studentsâ Mathematical Communication Skills Error in Form of Pictures on the Geometry of Space Subjectâ in EDUCARE: International Journal for Educational Studies, Volume 10(2), February, pp.87-94. Bandung, Indonesia and BS Begawan, Brunei Darussalam: Minda Masagi Press owned by ASPENSI and BRIMAN Institute, ISSN 1979-7877. Article Timeline: Accepted (December 13, 2017); Revised (January 15, 2018); and Published (February 28, 2018).